The Infulence of Online Marketing on Increasing Sales and Brand Awareness of MSME Product - Asra, Yunelly; Maulana, Hutomo Atman; Adam, Adam (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
This research aims to determine the effect of online marketing on increasing sales and brand awareness of MSME products assisted by PT. PHR in Duri, Mandau District. This type of research is Associative Descriptive. This study uses a quantitative approach. Sampling in the study used purposive random sampling technique, with 1,000 consumers who had purchased PT. PHR's MSME products online. Data testing was carried out using multiple linear regression analysis with the SPSS analysis tool. The results of this research are : Online Marketing has no partial influence on Brand Awareness. Increased Sales has a partial and negative Â influence on Brand Awareness. Online Marketing and Increased Sales have a significant effect on Brand Awareness simultaneously.